Exploration of High School Students' Difficulties on Newton's Law Material with Isomorphic Tests - Salsabila Indana Zulfa; Sentot Kusairi; Fatah Kurniawan (Kasuari: Physics Education Journal (KPEJ), 2025)
The research aims to analyze students' conceptual understanding of Newton's Law material by utilizing isomorphic tests. This quantitative descriptive research involved 30 male and 40 female respondents from class X MIPA of a private high school in Malang. Data was collected by survey method using a test consisting of 6 description questions adapted from the FCI instrument. The test, which consists of two groups of isomorphic items, has an inter-rater Cohen's kappa test reliability of 0.730 with a standard error of 0.059. Data analysis was carried out in a quantitative descriptive manner. Research found that students' understanding of concepts is very low. The highest score is given to students who understand the concept quite well. The category is based on isomorphic grouping. Students have difficulty in the implementation of Newton's Law II and Newton's Law III. Students' concept understanding is in the category of moderately understanding the concept. The difficulty experienced by students in the first indicator is that they cannot distinguish between the acceleration and speed of an object and assume that mass can affect the acceleration. In the second indicator, students explained that mass affects the interaction of forces